Models for integrating buprenorphine therapy into the primary HIV care setting. - Basu, Sanjay; Smith-Rohrberg, Duncan; Bruce, R Douglas; Altice, Frederick L (Clinical infectious diseases : an official publication of the Infectious Diseases Society of America, 2006)
Opiate dependence among human immunodeficiency virus (HIV)-infected patients has been associated with negative clinical outcomes, yet few affected patients receive appropriate and coordinated treatment for both conditions. The introduction of buprenorphine maintenance therapy into HIV care settings provides an opportunity for providers to integrate treatment for opiate dependence into their practices. Buprenorphine maintenance therapy has been associated with reductions in opiate use, increased social stability, improved adherence to antiretroviral therapy, and lowered rates of injection drug use. We describe the following 4 models for the integration of buprenorphine maintenance therapy into HIV care: (1) a primary care model, in which the highly active antiretroviral therapy-administering clinician also prescribes buprenorphine; (2) a model that relies on an on-site specialist in addiction medicine or psychiatry to prescribe the buprenorphine; (3) a hybrid model, in which an on-site specialist provides the induction (with or without stabilization phases) and the HIV care provider provides the maintenance phase; and (4) a drug treatment model that provides buprenorphine maintenance therapy services with HIV services in the substance abuse clinic setting. The key barriers against effective integration of buprenorphine maintenance therapy and primary HIV services are discussed, and we suggest several mechanisms to overcome such obstacles.
Keywords: Anti-HIV Agents; Antiretroviral Therapy, Highly Active; Buprenorphine; HIV Infections; Humans; Narcotic Antagonists; Opioid-Related Disorders; Primary Health Care